KINERJA DEPARTEMEN AKUNTANSI HOTEL BINTANG 5 DI DENPASAR DITINJAU DARI KOMITMEN, KOMPENSASI, KOMPETENSI, DAN MOTIVASI - Noni Mirantika; I Ketut Yudana Adi (Journal Research of Accounting, 2020)
The success and progress of a company is very much determined by the existence and existing human resources in controlling the company's operational activities. The accounting department as a central part in controlling operational activities is required to have good performance for the sustainability of the company. And it is appropriate for the management to pay attention to the accounting department employees by strengthening employee commitment, providing appropriate compensation, good competence and in accordance with their fields, as well as providing motivation that will improve employee performance. This research was conducted in the accounting department of 5-star hotels in Denpasar which aims to determine the influence of commitment, compensation, competence, and motivation on the performance of accounting department employees both influence partially or simultaneously. Data collection techniques are done by distributing questionnaires to respondents. The population in this study were 154 employees of the accounting department of a 5-star hotel in Denpasar. The sample used in this study were 129 employees. The sampling technique used in this study used a purposive sampling technique. Data analysis techniques used descriptive analysis, instrument test, classical assumption test, multiple linear regression analysis, t statistical test, f test, and test the coefficient of determination (R2). The results of the analysis show a regression model Y = 8.860 + 0.197X1 + 0.197X2 + 0.220X3 + 0.183X4. The conclusions obtained are commitment (X1), compensation (X2), competence (X3), and motivation (X4) partially and simultaneously have a positive and significant effect on the performance of the accounting department (Y). The magnitude of the influence of commitment (X1), compensation (X2), competence (X3), and motivation (X4) on the performance of the accounting department is 63.0% and the remaining 37.0% is influenced by other variables not examined in this study.Keywords: commitment, compensation, compensation, competence, motivation, performance.